Immunotherapy in chronic lymphocytic leukemia: advances and challenges - Pan Gao; Yang Zhang; Jun Ma; Ya Zhang (Experimental Hematology & Oncology)
Abstract Chronic lymphocytic leukemia (CLL) is characterized as a clonal proliferation of mature B lymphocytes with distinct immunophenotypic traits, predominantly affecting the middle-aged and elderly population. This condition is marked by an accumulation of lymphocytes within the peripheral blood, bone marrow, spleen, and lymph nodes. The associated immune dysregulation predisposes CLL patients to a higher risk of secondary malignancies and infections, which significantly contribute to morbidity and mortality rates. The advent of immunotherapy has revolutionized the prognosis of CLL, advancing treatment modalities and offering substantial benefits to patient outcomes. This review endeavors to synthesize and scrutinize the efficacy, merits, and limitations of the current immunotherapeutic strategies for CLL. The aim is to inform the selection of optimal treatment regimens tailored to individual patient needs. Furthermore, the review juxtaposes various therapeutic combinations to elucidate the comparative advantages of each approach, with the ultimate objective of enhancing patient prognosis and quality of life.